From Constructive Ambiguity to Escalating Commitment: The Evolution of the Bangladesh Accord as a Transnational Institution for Collective Action - Reinecke, Juliane; Donaghey, Jimmy (Administrative Science Quarterly, 2025)
We investigate a core challenge in building multi-stakeholder institutions for collective action: Constructive ambiguity—the deliberate use of imprecise language on a contested issue—is often needed to overcome conflict and enable agreement among parties. Yet, this initially enabling characteristic may complicate implementation when ambiguous commitments must be translated into concrete actions. To examine this challenge, we draw on an eight-year study of the Bangladesh Accord for Fire and Building Safety, an agreement among unions, NGOs, and more than 200 company signatories to end a series of deadly incidents that occurred in the Bangladesh garment sector. We reveal that, despite the risk of diluting the agreement during implementation, a multi-phase political process triggered a reinforcing process of escalating commitment, leading to the institution’s expansion in scale and scope. This process involved signatories negotiating more-stringent commitments, on the one hand, and stakeholder dynamics activating cascading layers of commitment enforcement, on the other, which drove signatories toward deeper institutional tie-in (i.e., stake) with the collective action institution. The process resulted in transforming constructive ambiguity into a catalyst for a robust collective action institution. We develop a model that explains how collective rationality can emerge and direct private interests to resolve transnational collective action problems.